Adaptive Modification of Amino Acid Pools in the Myocardium of a Long-Tailed Ground Squirrel Urocitellus undulatus at Different Stages of Hibernation - Karanova, M. V.; Zakharova, N. M. (Journal of evolutionary biochemistry and physiology, 2023)
The state of hibernation is characterized by an increased tolerance to long-term deep hypothermia, hypoxia, lack of food and water. At the same time, even a short-term reorganization of the adaptive mechanisms at low temperatures causes significant metabolic changes in animals, reflected in the amino acid profile. Metabolic changes in myocardial free amino acids during hibernation have not actually been studied, although the knowledge of these processes is important for deeper insight into the mechanisms of hibernation, relevant for clinical medicine. The aim of this work was to study the changes in the composition of myocardial free amino acids in a ground squirrel Urocitellus undulatus at different stages of hibernation. A negative interdependence of glutamic acid and alanine pools was revealed at different stages of torpor. The level of glutamic acid, as compared to the summer control (5.08 ± 0.44 µmol/g of wet weight), began to decline in the first (December) torpor bout, continued throughout prolonged torpor (down to 1.57 ± 0.14 µmol/g), and was accompanied by an increase in the alanine pool. During winter arousal, the glutamic acid pool rose above the summer level, while the alanine pool fell below that, with their total level remaining unchanged. Aspartic acid and glycine pools declined in parallel with the decrease in glutamate and aspartate pools, however, during winter arousal, glycine was not detected whatsoever. Given the involvement of glutamic acid and aspartate in anaplerotic reactions of the tricarboxylic acid (TCA) cycle and the reciprocal relationship of glutamic acid and alanine, it is concluded that the changes in the level of these metabolites at different stages of hibernation bouts reflect a gradual transition from aerobic (TCA cycle and oxidative phosphorylation) to anaerobic glycolysis, and vice versa during euthermia.